Case Analysis on the Abnormal Heating Defect of a 220kv XLPE Cable Intermediate Joint. Issue 1 (November 2020) - Hao, Zhang; Pengfei, Li; Guoqing, Ma; Zilong, Chen; Yubing, Duan; Xiaoli, Hu
Abstract: In this paper, through the infrared temperature measurement and high frequency partial discharge detection, we found an abnormal heating defect in the intermediate joint of 220kV cable. After dissecting the intermediate joint and measure the insulation resistance of internal epoxy components in the laboratory, the causes of the defects were analyzed. The overall heating of the middle joint of the cable shall be caused by the damp insulation. Partial discharge detection can not detect the cable insulation moisture defects. The effect of The infrared temperature measurement is good. After that, the hidden danger of the equipment was dealt with in time and a serious power grid accident is avoided. This case verifies the practicability of infrared temperature measurement in abnormal heating diagnosis of the cable line, and also verifies the limitations of partial discharge detection for internal damp fault diagnosis. This paper also points out the design defect of intermediate joint of similar structure, which provides the basis and reference for the future work.